# SOLUTION: Factor each polynomial by splitting the middle term and grouping 6x squared plus x minus 12 = the answer should be (2x plus 3)(3X MINUS 4) but I can't seem to get it ther

Algebra ->  Algebra  -> Polynomials-and-rational-expressions -> SOLUTION: Factor each polynomial by splitting the middle term and grouping 6x squared plus x minus 12 = the answer should be (2x plus 3)(3X MINUS 4) but I can't seem to get it ther      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Polynomials, rational expressions and equations Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Polynomials-and-rational-expressions Question 199293: Factor each polynomial by splitting the middle term and grouping 6x squared plus x minus 12 = the answer should be (2x plus 3)(3X MINUS 4) but I can't seem to get it there/ please help/thanksFound 2 solutions by rfer, checkley77:Answer by rfer(12675)   (Show Source): You can put this solution on YOUR website!multiply the factored form. (2x+3)(3x-4)= 6x^2+x-12 take (2x)(3x)=6x^2 (2x)(-4)+(3)(3x)=x (3)(-4)=-12 Answer by checkley77(12569)   (Show Source): You can put this solution on YOUR website!6x^2+x-12 The factors of 6 are (1 & 6), (-1 & -6), (2 & 3), (-2 &-3). The factors of 12 are (-1 & 12), (1 & -12), (-2 & 6), (2 & -6), (-3 & 4), (3 & -4). Now you need to select a set from each term that when multiplied together will equal +1, the middle term. Examples: Use the (1,6) & (-1,12) (1*-1)+(6*12)=-1*72=71 not close. Use the (2,3) & (-2,6) (2*-2)+(3*6)=-4+18=14 closer. Use the (2,3) & (-4,3) (2*-4)+(3*3)=-8+9=1 looks like a winner. Thus we have: (2x+3)(3x-4)using FOIL we get. 2x*3x=6x^2 2x*-4=-8x 3*3x=9x 3*-4=-12 6x^2-8x+9x-12 6x^2+x-12